Sosialisasi dan Evaluasi Aplikasi NextStep sebagai Sistem Rekomendasi Karier Bidang Teknologi Informasi pada Siswa Kelas 12 SMAN 1 Jatiwangi - Muhammad Rama Reyswara; Talitha Husna Salsabila; Khadiza Jannahanggita Nurhuda; Muhammad Hammam Mudhaffar (Jurnal Riset Multidisiplin Edukasi, 2026)
Proper career planning is very important for students, especially in the rapidly growing field of Information Technology (IT). However, a lack of understanding of career skills and interests often hinders students in determining the right career path. To address this issue, the NextStep application was developed based on artificial intelligence to provide IT career recommendations based on user skills. This study aims to evaluate the effectiveness of the socialization and acceptance of the NextStep application among 12th grade students at SMAN 1 Jatiwangi. The socialization activity was conducted online via Google Meet and evaluated through the collection of questionnaire data and interviews. The results of the analysis show that 85% of students felt helped by the career recommendations provided, 78% stated that the Resume Classification System feature was effective in understanding the relationship between skills and IT jobs, and 70% felt that the CV Builder feature made it easier to compile resumes. These findings conclude that NextStep is effective in helping students explore careers in IT and has the potential to be further developed to support more accurate career decision-making.